If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3(13 + -2) + -25 = 0 Combine like terms: 13 + -2 = 11 6 + 3(11) + -25 = 0 Multiply 3 * 11 6 + 33 + -25 = 0 Combine like terms: 6 + 33 = 39 39 + -25 = 0 Combine like terms: 39 + -25 = 14 14 = 0 Solving 14 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 | | 7+3a=11-a | | 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t | | 9-3x+5x=-11 | | 2-(x+3)=6 | | 5x+4=37 | | X^2+6x-34=0 | | y+x=y-x | | 2(x-5)+2x=x+3x-2x | | 180+(9x+4)=y | | 20-0.75x+0.55x=10 | | 55+8(25)=x | | 55+8=25 | | -1x^2+4=2x^2-5 | | -20=-10(x+12) | | .40=.5-12 | | 9x-8=9x+6 | | 5x+3(x-4)=8x-12 | | (7)(-6)= | | 12+8x-4=5+2(3x-1) |